The index of sustainable functionality: a new adaptive, multicriteria measurement of sustainability ? application to Western Australia. (4th October 2007) - Imberger, Jorg; Mamouni, Elena-Alexandra D.; Anderson, Jeni; Ng, May-Le; Nicol, Sam; Veale, Aaron
We define the functionality of systems in a geographic domain and use this definition to formulate a new quantitative indicator of sustainability, the Index of Sustainable Functionality (ISF). The ISF is a measure of the functionality of the processes underlying a particular standing stock and so provides a simple and objective assessment of the ability of a system to absorb an external or internal perturbation without losing the ability to recover. The ISF, for a geographic domain, is the sum of the values of quantitative indicators of the functionality of the underlying processes weighted by the stakeholders' priorities. To illustrate the methodology, we derive the ISF for the State of Western Australia and showed that, for Western Australia, economic measures of progress such as the Gross State Product used by the Government to guide the policies of the state, do not adequately reflect changes in our quality of life or the health of the ecosystem.